2021
DOI: 10.3389/fpls.2021.639154
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Traits of Two Major Arabidopsis Accessions, Col-0 and Ws, Under Salinity

Abstract: Salinity affects plant growth and development as shown with the glycophyte model plant, Arabidopsis thaliana (Arabidopsis). Two Arabidopsis accessions, Wassilewskija (Ws) and Columbia (Col-0), are widely used to generate mutants available from various Arabidopsis seed resources. However, these two ecotypes are known to be salt-sensitive with different degrees of tolerance. In our study, 3-week-old Col-0 and Ws plants were treated with and without 150 mM NaCl for 48, 72, or 96 h, and several physiological and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 138 publications
2
7
0
Order By: Relevance
“…It suggests that salt stress may affect plant growth by affecting water usage in the shoots and thus disrupting the photosynthetic system. Previous studies have shown that photosynthesis is impaired in plants under salt stress [ 25 , 26 , 27 ], which is in agreement with this study. Polyamines, amides, and biogenic amines were significantly enriched in the leaves and roots of Fanni and Longya10, further validating that those polyamines play an essential role in the plant’s response to abiotic stress [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…It suggests that salt stress may affect plant growth by affecting water usage in the shoots and thus disrupting the photosynthetic system. Previous studies have shown that photosynthesis is impaired in plants under salt stress [ 25 , 26 , 27 ], which is in agreement with this study. Polyamines, amides, and biogenic amines were significantly enriched in the leaves and roots of Fanni and Longya10, further validating that those polyamines play an essential role in the plant’s response to abiotic stress [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, salt stress significantly affected the galactose metabolism and flavonoid biosynthesis of rice [46]. In our study, NaCl stress up-regulated the arabinan catabolic process, lignin catabolic process and flavonoid biosynthetic process of the host plant and some studies illustrated these processes played an important role in helping the plant to adapt to salt stress [56,57]. Therefore, the synthesis of secondary metabolites vulnerable to salt stress and the function of secondary metabolites includes the protection from the damage of reactive oxygen species and the enhancement of the resistance of the cell wall [58].…”
Section: Discussionmentioning
confidence: 50%
“…Similar to CDPK6/CPK3 salt-stress induction, over-expression of native CPK1 resulted in increased salinity tolerance in cell culture (Veremeichik et al, 2021), reinforcing a potential link between diel CPK-mediated phosphorylation events and the ability to mitigate abiotic stress. Alternatively, WAK1 has been implicated in maintaining cell wall integrity (Leschevin et al, 2021), which has diel plant cell growth implications that may contribute to the large mesophyll cell phenotype of rve 4 6 8 plants (Gray et al, 2017).…”
Section: Discussionmentioning
confidence: 99%